Synthesis and physico-chemical characterization of PH sensitive hydrogels and their applications in drug delivery / Shahid Bashir - Shahid, Bashir (2017)
Environmentally sensitive hydrogels have been investigated as smart drug delivery systems capable to release drug at the appropriate time and site of action. In the present work, N-succinyl chitosan was prepared by modification of chitosan using succinic anhydride in acetic acid/methanol solution. Then, pH-sensitive semi-interpenetrating network hydrogels of N-succinyl chitosan/ poly (acrylamide-co-acrylic acid) were prepared by crosslinking of N-succinyl-chitosan and poly (acrylamide-co-acrylic acid) via Schiff base mechanism using glutaraldehyde as a crosslinking agent. On the other hand, N-succinyl chitosan-g-poly (acrylamide-co-acrylic acid), N-succinyl chitosan-g-poly (acrylic acid), N-succinyl chitosan-g-poly (methacrylic acid), and Karaya gum-g-poly (acrylic acid) hydrogels were prepared using ammonium persulfate as an initiator and N, N’-methylenebisacrylamide as a crosslinking agent, through free radical mechanism. The successful of the synthesis of hydrogels were confirmed by their physico-chemical characterization using Fourier transform infrared analysis, X-ray diffraction analysis, and differential scanning calorimetric analysis. The surface morphology of hydrogels was observed under field emission scanning electron microscope and suggests the highly porous network structures of the synthesized hydrogels. The yield (%), gel contents (%), and gel time was observed which was dependent on the hydrogels composition. The rheology study was performed to measure the mechanical strength. Moreover, swelling study revealed that hydrogels were highly swellable and depended on the hydrogel composition, pH, type and concentration of salt solutions. Swelling kinetics was evaluated and swelling ratio of hydrogels followed non-linear second order rate equation. Encapsulation efficiency of the hydrophilic 5-fluorouracil (5-FU) in N-succinyl chitosan/ poly (acrylamide-co- acrylic acid) and theophylline in N-succinyl chitosan-g-poly (acrylamide-co- acrylic acid), N-succinyl chitosan-g-poly (acrylic acid), N-succinyl chitosan-g-poly (methacrylic acid) hydrogels Environmentally sensitive hydrogels have been investigated as smart drug delivery systems capable to release drug at the appropriate time and site of action. In the present work, N-succinyl chitosan was prepared by modification of chitosan using succinic anhydride in acetic acid/methanol solution. Then, pH-sensitive semi-interpenetrating network hydrogels of N-succinyl chitosan/ poly (acrylamide-co-acrylic acid) were prepared by crosslinking of N-succinyl-chitosan and poly (acrylamide-co-acrylic acid) via Schiff base mechanism using glutaraldehyde as a crosslinking agent. On the other hand, N-succinyl chitosan-g-poly (acrylamide-co-acrylic acid), N-succinyl chitosan-g-poly (acrylic acid), N-succinyl chitosan-g-poly (methacrylic acid), and Karaya gum-g-poly (acrylic acid) hydrogels were prepared using ammonium persulfate as an initiator and N, N’-methylenebisacrylamide as a crosslinking agent, through free radical mechanism. The successful of the synthesis of hydrogels were confirmed by their physico-chemical characterization using Fourier transform infrared analysis, X-ray diffraction analysis, and differential scanning calorimetric analysis. The surface morphology of hydrogels was observed under field emission scanning electron microscope and suggests the highly porous network structures of the synthesized hydrogels. The yield (%), gel contents (%), and gel time was observed which was dependent on the hydrogels composition. The rheology study was performed to measure the mechanical strength. Moreover, swelling study revealed that hydrogels were highly swellable and depended on the hydrogel composition, pH, type and concentration of salt solutions. Swelling kinetics was evaluated and swelling ratio of hydrogels followed non-linear second order rate equation. Encapsulation efficiency of the hydrophilic 5-fluorouracil (5-FU) in N-succinyl chitosan/ poly (acrylamide-co- acrylic acid) and theophylline in N-succinyl chitosan-g-poly (acrylamide-co- acrylic acid), N-succinyl chitosan-g-poly (acrylic acid), N-succinyl chitosan-g-poly (methacrylic acid) hydrogels